Menumbuhkan Sikap Percaya Diri Siswa pada Pembelajaran di Kelas - Muhammad Zaki Allana Al Firdaus (Proceedings Series of Educational Studies, 2023)
Abstract: A student is someone at a stage of growth and development, where growth and development is a sign that the student needs guidance or direction by the teacher. Thus, it is necessary to have a good provision so that students have good advantages or skills or are proficient later after they leave the educational institution. The method used in the preparation of this article is analysis in journals and other articles related to students. The participation of students or students in the learning process is one of the objectives of learning. The existence of participation, activeness, and good interaction between teachers and students will increase confidence in students. Teaching and learning activities that run interactively will be normative because there is value in it. The interaction of teachers and students must be active and also educative. In this case a student is active mentally, attitudes, and also deeds.Keywords: confident; student; Learning Abstrak: Siswa merupakan seseorang pada tahap pertumbuhan dan perkembangan, yang mana pertumbuhan dan perkembangannya adalah tanda bahwa siswa itu yang memerlukan bimbingan atau arahan oleh guru. Dengan demikian perlu suatu ketentuan yang bersifat baik supaya siswa memiliki kelebihan atau keahlian yang bagus atau mahir nantinya di saat setelah ia keluar dari lembaga pendidikan. Metode yang digunakan pada penyusunan artikel ini adalah analisis pada jurnal dan artikel lain yang berkaitan dengan peserta didik. Partisipasi peserta didik atau siswa dalam proses pembelajaran merupakan salah satu tujuan adanya pembelajaran. Adanya partisipasi, keaktifan, serta interaksi yang baik antara guru dan peserta didik akan meningkatkan kepercayaan diri pada siswa. Aktivitas belajar mengajar yang berjalan interaktif akan bernilai normatif karena terdapat nilai di dalamnya. Interaksi guru dan siswa harus aktif dan juga edukatif. Dalam hal ini seorang siswa aktif secara mental, sikap, dan juga perbuatan.Kata kunci: percaya diri; siswa; pembelajaran